Rattan spines as deterrence? A spinescence study on different species of rattans. (2nd October 2020) - Liu, Kunpeng; Mansor, Asyraf; Ruppert, Nadine; Fadzly, Nik
ABSTRACT: Rattan spines are most often regarded as an identification trait and perhaps as a physical protection structure. In this study, we study the spinescence traits from five different species rattan: Daemonorops lewisiana, Daemonorops geniculata, Calamus castaneus, Plectomia griffithii, and Korthalsia scortechinii . We tested length, width, angle, strength, spine density, cross-section surface, spine color, and leaf trichomes (only for D. lewisiana, C. castaneus and D. geniculata ). We also tested whether the spines were capable of deterring small climbing mammals (for Plectomia griffithii and Calamus castaneus ) by using a choice selection experiment. Due to a variety of spine traits, we could not categorize whether any species is more or less spinescent than the others. We suggest that spines have a much more significant role than merely as a physical defense and work together with other rattan characteristics. This is also evidenced by our choice selection experiment, in which the spines on a single stem donot deter small climbing mammals. However, this is a work in progress, and we have outlined several alternative methods to be used in future work.